RP-HPLC METHOD DEVELOPMENT AND VALIDATION FOR THE ESTIMATION OF PANTOPRAZOLE IN BULK AND PHARMACEUTICAL DOSAGE FORMS - FARAAT ALI, (International Journal of Pharma and Bio Sciences, 2015)
A simple, precise, sensitive and rapid reverse phase high performance liquid chromatographic method was developed for the estimation of Pantoprazole in bulk and pharmaceutical dosage forms. The method was developed by using Waters X-Bridge C-18(4.6×150 mm, 5µm) column; mobile phase consisting of ACN and bicarbonate buffer at pH 9.0; the flow rate of 1.0 ml/min and detection wavelength 214nm and eluted at 4.775 min. The linearity ranges were 25 to 125ppm for Pantoprazole. The method was validated as per ICH guidelines for various parameters like linearity, precision, accuracy, LOD, LOQ and robustness. The validated method was applied to the commercially available pharmaceutical dosage forms and obtained the desired result.